Ethnomathematics and Renewable Education in the Village of Tanjungjaya Village, Panimbang District, Pandeglang Regency, Banten - S, Deva Putra (Research Collaboration Community (RCC), 2024)
This study explores the integration of ethnomathematics and renewable education in Pandeglan village, Tanjung Jaya, Banten, Indonesia. Using a qualitative case study approach, it explores how indigenous mathematical practices can be integrated into formal education alongside modern technology. The findings reveal that ethnomathematics is deeply embedded in the daily life of the village, especially in agriculture and traditional crafts. Local practices show that geometry and measurement concepts are intuitively applied. In schools, teachers are beginning to incorporate these cultural elements into math lessons, increasing students' motivation and understanding. Some schools demonstrate their commitment to renewable education by adopting computer technology and internet-based teaching materials. However, there are significant implementation challenges, such as limited infrastructure and insufficient teacher training in educational technology. The integration of ethnomathematics and renewable education shows promise in developing students' mathematical and cultural understanding. This approach connects abstract concepts to familiar contexts while introducing modern learning tools. Challenges faced include inadequate technology access, unstable internet connections and teachers' low proficiency with digital tools. The study recommends improving technology infrastructure, conducting regular teacher trainings, developing culturally appropriate educational practices, and fostering collaboration between schools, government and higher education institutions. In conclusion, the study shows that combining ethnomathematics and renewable education has the potential to improve the quality of education in rural areas. It highlights the importance of contextualizing learning within local culture while using modern educational technologies. With appropriate support and implementation, this integrated approach can serve as a model for strengthening education in similar rural contexts